The impact of anticipated stigma on psychological and physical health problems in the unemployed group - O’Donnell, Aisling T.; Corrigan, Fiona; Gallagher, Stephen (Frontiers in Psychology, 2015)
Previous research has demonstrated that the unemployed suffer increased psychological and physical health problems compared to their employed counterparts. Further, unemployment leads to an unwanted new social identity that is stigmatizing, and stigma is known to be a stressor causing psychological and physical health problems. However, it is not yet known whether being stigmatized as an unemployed group member is associated with psychological and physical health in this group. The current study tested the impact of anticipated stigma on psychological distress and physical health problems, operationalized as somatic symptoms, in a volunteer sample of unemployed people. Results revealed that anticipated stigma had a direct effect on both psychological distress and somatic symptoms, such that greater anticipated stigma significantly predicted higher levels of both. Moreover, the direct effect on somatic symptoms became non-significant when psychological distress was taken into account. Thus, to the extent that unemployed participants anticipated experiencing greater stigma, they also reported increased psychological distress, and this psychological distress predicted increased somatic symptoms. Our findings complement and extend the existing literature on the relationships between stigmatized identities, psychological distress and physical health problems, particularly in relation to the unemployed group. This group is important to consider both theoretically, given the unwanted and transient nature of the identity compared to other stigmatized identities, but also practically, as the findings indicate a need to orient to the perceived valence of the unemployed identity and its effects on psychological and physical health.